2002
DOI: 10.1590/s1519-69842002000300010
|View full text |Cite
|
Sign up to set email alerts
|

On two methods to estimate production of Eichhornia crassipes in the eutrophic Pampulha reservoir (MG, Brazil)

Abstract: This paper deals with variations in biomass and in the production of Eichhornia crassipes (water hyacinth) in a eutrophic tropical reservoir. Net production was assessed by both a traditional method and a demographic approach. The initial biomass ranges from 96 g DW.m -2 to a maximum of 2027 g DW.m -2 . Net production estimates varied greatly according to which method was used to calculate them (traditional: 20.6 ton DW.hectare -1 .year -1 , demographic: 226.9 ton DW.year -1 ).Key words: Eichhornia crassipes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
1
4
1
Order By: Relevance
“…The maximum total biomass of water hyacinth, as indicated in the present study (109 t/DM/ha), was lower than that in some tropical and sub‐tropical countries such as Brazil (203 t/DM/ha: Greco & Freitas ) and Mexico (284 t/DM/ha: Gutiérrez et al ). The high biomass in these tropical and sub‐tropical countries could be a result of favorable conditions for its growth because these Meso‐American countries represent the native range of its distribution (Shaltout ).…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…The maximum total biomass of water hyacinth, as indicated in the present study (109 t/DM/ha), was lower than that in some tropical and sub‐tropical countries such as Brazil (203 t/DM/ha: Greco & Freitas ) and Mexico (284 t/DM/ha: Gutiérrez et al ). The high biomass in these tropical and sub‐tropical countries could be a result of favorable conditions for its growth because these Meso‐American countries represent the native range of its distribution (Shaltout ).…”
Section: Discussioncontrasting
confidence: 65%
“…The growth pattern of water hyacinth in the Nile Delta was similar to that of the same species in Brazil (Greco & Freitas ), Mexico (Gutiérrez et al ), the USA (Akbay et al ) and China (Liu et al ). In the Nile Delta, the total biomass of water hyacinth reached peak values in August, which differs from the study of Center and Spencer (), who reported that the total biomass of water hyacinth growing in Lake Alice (Florida, USA) peaked in mid‐June and gradually declined thereafter.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Species with a high aeration capacity and a powerful convective gas‐flow system, including P. australis , T. angustifolia and Eleocharis sphacelata (Armstrong et al , Brix et al ), are widely distributed in various habitats such as oligo‐mesotrophic fens (Wheeler and Proctor , Nakamura et al , Sorrell and Hawes ), meso‐eutrophic ponds (Hejny and Husak ), deep anoxic lakes dominated by NH (Yamasaki , Weisner and Strand , Wheeler and Proctor , Inoue and Tsuchiya , Sorrell and Hawes ) and NO‐abundant oxic sites at shallow‐lake fringes and meadows (Kühl et al ). In contrast, species with a low aeration capacity, such as Z. latifolia , Eichhornia crassipes , Schoenoplectus tabernaemontani , Trapa natans and Scirpus tabernaemontani , tend to appear only in eutrophic and anaerobic habitats (Center and Spencer , Yamasaki , Kurihara and Ikusima , Greco and De Freitas , Anderson and Mitsch , Xiao et al ).…”
Section: Discussionmentioning
confidence: 99%
“…E. crassipes has the enormous advantage of changing water parameters, most notably reducing the water temperature [29]. According to Greco and de Freitas [30], this macrophyte grows best at high temperatures, as experienced in Brazil. E. crassipes has previously been tested for the phytoremediation of urban wastewater [31], cyanide [32], and mercury [33] and has been assessed as useful and appropriate for such purposes.…”
Section: Second Trial and Final Layoutmentioning
confidence: 99%